Indução de mecanismos bioquímicos de defesa em sorgo (Sorghum bicolor) por frações obtidas do decocto de avenca (Adiantum capillus-veneris) - Meinerz, Cristiane Claudia (2010)
Induction of resistance involves the activation of plant defense mechanisms in response to treatment with biotic or abiotic elicitors. The application of plant extracts in order to induce resistance mechanisms is an interesting alternative to chemical control, however, besides the presence of inducers, can occur the presence of suppressors. This study aimed to partially purificate through gel filtration chromatography (GFC) and precipitation with ammonium sulfate (SA), compounds present in decoct of Adiantum capillus-veneris, capable to induce defense mechanisms in sorghum mesocotyls, including phytoalexins and peroxidase, polyphenoloxidase (PPO), phenylalanine ammonia-lyase (PAL) and chitinase. The decoct 1% was fractionated with concentrations of ammonium sulfate, 0-20%, 20-40%, 40-60%, 60-80% and 80-100% of SA and those fractions were subjected to GFC. We obtained nine protein peaks and one glucosic peak for decoct with molecular weights ranging from 0.61 to 0.01 KDa; to fraction 0-20% were obtained two protein and two glucosic peaks, with molecular weights lower than 0.01 KDa, and concentration of sugars ranging from 4.1 to 17.5 mg mL-1; to fraction 20-40% were obtained three protein peaks (0.98 to 111.5 KDa) and five glucosic peaks (11.3 to 73.7 mg mL-1); to fraction 40-60% were obtained two protein peaks (0.09 to 111.5 KDa) and two glucosic peaks (5.6 to 7.5 mg mL-1); to fraction 60-80% were obtained six protein peaks (lower than 0.02 KDa) and two glucosic peaks (16.5 to 51.3 mg mL-1); and to fraction 80-100% were obtained three protein peaks (lower than 0.09 KDa). Sorghum mesocotyl were treated with fractions from the GFC, and decoct, acibenzolar-S-methyl (ASM) (125 mg L-1 of a. i. as elicitor of reference) and sodium phosphate buffer 10 mM pH 6.0. After incubation of 96 h were measured the levels of phytoalexins in mesocotyls and the activity of defense-related enzymes in leaves. Treatment with peak II (0,09 KDa) induced phytoalexin 6.68% more than. Among the fractionn, 60-80% increased 76% compared to ASM. To peroxidase the peak IV (lower than 0,01 KDa) increased 21% the activity compared to control water, and 44% compared to ASM. For the fraction 0-20% the protein peak II (lower than 0,01 KDa) increased 39% the activity in relation to the fraction 0-20% and 19% in relation to decoct. The fraction, 80-100% increased 89% compared to, ASM. For the PPO the peak VI (lower than 0,01 KDa) from decoct decreased 88% the activity compared to ASM. For PAL the peak II (lower than 0,01 KDa) from fraction 0-20% was 91% higher than decoct. For chitinase 1% peak IV (lower than 0,01 KDa) from decoct was 68% higher than the ASM. It was possible to induce defense mechanisms in sorghum by the application of partially purified fractions from A. capillus-veneris, which can allow to obtain new molecules and development alternative methods to control plant diseases